Welcome to Westonci.ca, where you can find answers to all your questions from a community of experienced professionals. Connect with a community of professionals ready to provide precise solutions to your questions quickly and accurately. Get detailed and accurate answers to your questions from a dedicated community of experts on our Q&A platform.

find AB given A(-4,1) and B(3,-1)​

Sagot :

Answer:

here,

A= (-4,1)= (x1,y1)

B= (3,-1)=(x2,y2)

now,

by using distance formula,

AB^2= (x2-x1)^2+(y2-y1)^2

=(3-(-4))^2+(-1-1)^2

=(3+4)^2+(-2)^2

=49+4

=53

AB= root under 53